1980
DOI: 10.1177/00220345800590051501
|View full text |Cite
|
Sign up to set email alerts
|

Basic Biological Sciences

Abstract: Of 50 strains of lactobacilli isolated from dental plaque of school children, two strains, provisionally identified as Lactobacillus salivarius, and one strain, provisionally identified as Lactobacillus fermentum, induced significant caries activity in conventional hamsters. Sucrose was a required dietary cariogenic substrate and could not be replaced with glucose or starch. In contrast to cariogenic strains of Streptococcus mutans the active lactobacilli did not form adherent sucrose-mediated plaques in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…as well as their impact on the mixed-species consortium. In an early animal model study by Fitzgerald et al (Fitzgerald et al, 1980 ), it was found that clinic isolates of L. salivarius and L. fermentum were able to induce significant carious activity in conventional hamsters but not on hamsters whose regular oral flora was depressed via polyantibiotics. This also indicates results of likely interactions between members of the indigenous oral flora and the lactobacilli infected.…”
Section: Discussionmentioning
confidence: 99%
“…as well as their impact on the mixed-species consortium. In an early animal model study by Fitzgerald et al (Fitzgerald et al, 1980 ), it was found that clinic isolates of L. salivarius and L. fermentum were able to induce significant carious activity in conventional hamsters but not on hamsters whose regular oral flora was depressed via polyantibiotics. This also indicates results of likely interactions between members of the indigenous oral flora and the lactobacilli infected.…”
Section: Discussionmentioning
confidence: 99%
“…They are mostly thought to be transient in the mouth and their numbers on the tooth surfaces of healthy infants and young children are usually low [ 5, 6, 19 ]. Low affinity to the tooth surface is thought to be the major factor that contributes to its low prevalence in the plaque microbiota of healthy individuals [ 8, 10 ]. However, lactobacilli tend to increase in numbers with increasing intake of fermentable sugars in the diet, a situation that is also conducive to dental caries.…”
Section: Major Lactobacillus Species In De...mentioning
confidence: 99%
“…Recent studies by Caufield et al showed that about half of the L. fermentum analysed possesses the genes for the extracellular glucans, but they were remarkably absent in other species associated with severe childhood caries [ 5 ]. No evidence suggests that lactobacilli synthesize any major adhesive EPS from sucrose [ 8, 36 ] , which in S. mutans is predominantly α [3,1]-linked and known to play a central role in its adherence and cariogenicity [ 37 ].…”
Section: Sugar Fermentation and Acid Productionmentioning
confidence: 99%
See 2 more Smart Citations